Granulicatella adiacens as an Unusual Cause of Empyema: A Case Report and Review of Literature - Purohit, Geetarani; Mishra, Baijayantimala; Sahoo, Satyajeet; Mahapatra, Ashoka (Journal of Laboratory Physicians, 2022)
Granulicatella adiacens, a nutritionally variant Streptococcus (NVS), is part of the normal commensal flora of human mouth, genital, and intestinal tracts and rarely causes disease. It has been mostly reported from bacteremia and endocarditis cases, but rarely can cause vertebral osteomyelitis, pancreatic abscess, otitis media, and endovascular, central nervous system, ocular, oral, bone and joint, and genitourinary infections. Due to requirement of fastidious culture conditions and non-specific colony morphology, serious diagnostic difficulties may arise in cases of NVS infections. Here, we are reporting a rare fatal infection of G. adiacens presented with empyema complicated to sepsis and necrotizing fasciitis.Clinicians should be aware of the pathogenic potential of Granulicatella adiacens (a normal commensal flora of human mouth, genital and intestinal tracts). Appropriate supplemented media and a reliable detection system should be used to identify these fastidious organisms. We present this rare case to bring awareness among clinicians regarding such a rare but potentially fatal infection.
Keywords: empyema; Granulicatella adiacens; nutritionally variant Streptococcus; sepsis